Associations between disease severity, depression, health-related quality of life, and physical activity in adults with sickle cell disease - Adekola B. Ademoyegun; Mutiu A. Adeyemo; Babatunde Y. Adewuyi; Adebukola G. Ibitoye; Olalekan I. Akerele; Taofeek O. Awotidebe; Chidozie E. Mbada (Bulletin of Faculty of Physical Therapy)
Abstract Background Individuals with sickle cell disease (SCD) are faced with a plethora of challenges that affect their quality of life, mood, and physical and social participation. Physical activity (PA) is known to reduce inflammatory activity and enhance psychosocial health in individuals with chronic illnesses; however, there exist controversies on the role of PA in disease severity (DS), depression, and health-related quality of life (HRQoL) in SCD. Objective This study aimed to assess the role of PA in the level of DS, depression, and HRQoL in SCD and investigate mediation models among DS, depression, HRQoL, and PA in adults with SCD. Methods A total of 385 patients with SCD (mean age 35.45 ± 12.01 years; 51.70% female) attending hematology clinics in two Nigerian tertiary hospitals participated in this cross-sectional study. Data on DS, depression, HRQoL, and PA were assessed through modified disease severity scoring protocol, patient health questionnaire-9, 12-item short-form health survey, and international physical activity questionnaire short-form, respectively. Multiple hierarchical regression and mediation analyses were applied. Results The findings show that 53.5% are physically inactive, and PA accounts for 27.50%, 18.40%, 38.80%, and 8.50% of the variance observed in DS, depression, and physical component summary (PCS-12) and mental component summary (MCS-12) of HRQoL, respectively. There was a significant mediating role of DS in the relationship between PA and depression (β =  − 0.0026; LLCI − 0.0031; ULCI − 0.0022), PCS-12 (β = 0.0019; LLCI 0.0013; ULCI 0.0024), and MCS-12 (β = 0.0009; LLCI 0.0001; ULCI 0.0018). The relationship between DS and depression was mediated only through PCS-12 (β = 0.2975; LLCI 0.1825; ULCI 0.4066). Similarly, only PCS-12 significantly mediated the relationship between PA and depression (β =  − 0.0021; LLCI − 0.0026; ULCI − 0.0017). Conclusion Individuals with SCD with high levels of PA have low levels of DS and symptoms of depression and reported better HRQoL. Furthermore, patients with better HRQoL, especially physical health showed low depressive symptoms in adults with SCD. Clinicians and policymakers should consider incorporating PA assessments and interventions into the care of patients with SCD. The formulation of specific PA guidelines for patients with SCD is also warranted.